Mock-object generation with behavior - Tillmann, Nikolai; Schulte, Wolfram (21st IEEE/ACM International Conference on Automated Software Engineering, 2006. ASE '06, 2006)
Unit testing is a popular way to guide software development and testing. Each unit test should target a single feature, but in practice it is difficult to test features in isolation. Mock objects are a well-known technique to substitute parts of a program which are irrelevant for a particular unit test. Today mock objects are usually written manually supported by tools that generate method stubs or distill behavior from existing programs. We have developed a prototype tool based on symbolic execution of .NET code that generates mock objects including their behavior by analyzing all uses of the mock object in a given unit test. It is not required that an actual implementation of the mocked behavior exists. We are working towards an integration of our tool into Visual Studio Team System